THE ROLE OF SHARIA AND LITERACY RETURNS ON INTEREST SAVING IN SHARIA BANK (Case study of Economics Faculty Students and Wijaya Putra University Business Surabaya) - Mochammad Rizal Fanani; Erwan Aristyanto (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
This research aims to examine the impact of sharia financial literacy and interest rates on savings in sharia banks among students at the Faculty of Economics and Business, Wijaya Putra University, Surabaya. This research uses a quantitative research approach. The population consists of 676 students who are currently registered at the Wijaya Putra Faculty of Economics and Business. So after calculating using the Slovin Formula, from the total population we obtained a sample of 87 people. Using a Structural Equation Model (SEM) approach, specifically based on Partial Least Squares (PLS), a type of SEM that focuses on components or variance. The results of the research show that Sharia Literacy has a significantly positive effect on Interest in Saving, Returns have an effect but are not significant on Interest in Saving, Sharia Literacy and Returns have an effect but are not significant on Interest in Saving